Peace operations in the francophone world global governance meets post-colonialism - Charbonneau, Bruno; Chafer, Tony (Cass series on peacekeeping, 2014)
This book critically examines peacebuilding, humanitarian intervention and peace operation practices and experiences in francophone spaces.Francophone Africa as a specific space is relatively little studied in the peace and security literature, despite the fact that almost half of all peacekeepers are deployed or were deployed in this part of Africa during the last decade. It is an arena for intervention that deserves more serious attention, if only because it provides fertile ground for exploring the key questions raised in the peacekeeping and peacebuilding literature. For instance, in 2002 a French operation (Licorne) was launched and in 2003 a UN force was deployed in Côte d'Ivoire alongside the French force there.Filling a gap in the current literature, Peace Operations in the Francophone World critically examines peacekeeping and peacebuilding practices in the francophone world, including but not limited to conflict prevention and resolution, security sector reform (SSR), francophone politics, and North--South relations. The book explores whether peace and security operations in francophone spaces have exceptional characteristics when compared with those carried out in other parts of the world and assesses whether an analysis of these operations in the francophone world can make a specific and original contribution to wider international debates about peacekeeping and peacebuilding.This book will be of much interest to students of peacekeeping, peacebuilding, peace and conflict studies, African politics, security studies, and IR in general